English File. Intermediate: student's book - Latham-Koenig C. Christina (Oxford, Oxford University Press, 2019)
The Student's Book includes: motivating, real-world texts, grammar bank with rules and exercises, illustrated vocabulary bank and sound bank, practical English focus on everyday language.Topics: Food and restaurants, sport, family and personality, money, transport and travel, mobile phones, describing people, education, houses, friendship, work, shopping, cinema, what people do, television.